Tax compliance and representation in Zambia’s informal economy - Resnick, Danielle (International Food Policy Research Institute, 2019)
What drives tax compliance among informal workers and does it affect demands for political representation? While these questions have been posed previously in political economy scholarship, there are few studies that examine these dynamics among informal workers, who constitute the majority of the population in developing countries. Contrary to assumptions that informal workers fall outside the tax net, they often encounter a variety of taxes collected by national and local authorities. Based on an original survey with 823 informal workers across 11 markets in Zambia’s capital, Lusaka, and interviews with relevant policymakers, this paper finds that compliance tends to be higher among those workers operating in markets with better services, providing support for the fiscal exchange hypothesis. Moreover, using a vote choice experiment, I find that those who pay taxes, regardless of how much they pay, are more likely than those who do not to vote for a hypothetical mayoral candidate interested in improving market services and stall fees rather than one interested in broader social goods, such as improving education and schools in Lusaka. The results suggest that even among a relatively poor segment of the population, tax revenue can be mobilized if the benefits of those taxes are directly experienced and that just the process of paying taxes can affect an individual’s demand for representation by policymakers.